Creation of a linked cohort of children and their parents in a large, national electronic health record dataset. Issue 32 (13th August 2021) - Angier, Heather; Giebultowicz, Sophia; Kaufmann, Jorge; Heintzman, John; O'Malley, Jean; Moreno, Laura; DeVoe, Jennifer E.
Abstract : Abstract: To examine which parental health care and health factors are most strongly associated with a child's receipt of recommended care we must be able to link children to their parents in electronic health record data. Yet, there is not an easy way to link these data. To identify a national cohort of children that link to at least one parent in the same electronic health record dataset and describe their demographics. Methodology to link parents and children in electronic health records and descriptive sociodemographic data. Children with at least one encounter with a primary care clinician between Januray 1, 2007 and December 12, 2018 to a community health center in the OCHIN national network. We identified parents of these children who also had at least one encounter to a community health center in the network using emergency contact and guarantor record fields. A total of 227, 552 children had parents with a linkable patient record. After exclusions, our final cohort included 213, 513 distinct children with either one or two parent-links. 82% of children linked to a mother only, 14% linked to a father only, and 4% linked to both a mother and a father. Most families consisted of only one linked child (61%). We were able to link 33% of children to a parent in electronic health record data from a large network of community health centers across the United States. Further analyses utilizing these linkages will allow examination of the multi-level factors that impact a child's receipt of recommended health care. Abstract : Supplemental Digital Content is available in the text